Lifespan Development A Psychological Perspective - Lally, Martha; Valentine-French, Suzanne (Open textbook library., 2023)
Developmental Psychology, also known as Human Development or Lifespan Development, is the scientific study of ways in which people change, as well as stay the same, from conception to death. You will no doubt discover in the course of studying that the field examines change across a broad range of topics. These include physical and other psychophysiological processes, cognition, language, and psychosocial development, including the impact of family and peers.